PENERAPAN PERLINDUNGAN HUKUM TERHADAP SAKSI DALAM PROSES PERADILAN PIDANA KASUS KORUPSI - Fransiskus Dodi (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2013)
This legal research entitled The Implementation of Legal Protection to the Victims in Process of Criminal Trial of Corruption. This background of this research was, the victims have not been pcotected in providing information either before the investigator or the court, in particularly the reporting witness of which submit report of the existence of criminal action of corruption. The emerging case was the position of victim as the verifying materials that hold important role in the verification process of a trial of criminal action of corruption, thus it causes the witness should be legally protected. How is the shape and practice of protection of which is given to the witness in the case of corruption criminal action and what barriers make the witness difficult to gain legal protection. In this legal writing, the author used normative juridical research method and sociological juridical method, wherein data analysis used was descriptive and qualitative methods, i.e. collected data will behalf as sources in drawing conclusion if the implementation of protection to the victim has been conducted appropriately to the theoretical principles of valid laws. The result of author’s research is that up to now the implementation of protection to the witness has not been conducted optimally, although there has been any legal shield protecting to the victim.